An unconventional two-stage cultivation strategy to increase the lipid content and enhance the fatty acid profile on Chlorella minutissima biomass cultivated in a novel internal light integrated photobioreactor aiming at biodiesel production - Amaral, Mateus S.; Loures, Carla C. A.; Pedro, Guilherme A.; Reis, Cristiano E. R.; De Castro, Heizir E.; Naves, Fabiano L.; Silva, Messias B. [UNESP]; Prata, Arnaldo M. R. (Elsevier B.V., 2020)
Biodiesel quality is dependent upon the fatty acids distribution of the raw material used in the trans/esterification reactions. While microalgae cells are regarded as potential oil suppliers for the biodiesel production chain, a common criticism is related to the low lipid productivities and often to a poor fatty acid distribution. In the present work we propose to submit microalgal cultivation to a second stage with nutritional stress by a simple addition of a 70% nitrate source depleted medium at the beginning of stationary phase, without harvesting cells, saving time and water. Chlorella minutissima was cultivated in a novel unconventional photobioreactor, named Internally Illuminated Integrated Photobioreactor (ILIPBR), to verify the efficiency of the proposed strategy. Biomass concentration, lipid content and volumetric lipids productivity increased 24.9%, 120.7% and 55.6%, respectively, from Stage 1 to Stage 2, when ILI-PBR was illuminated by constant blue LED and 0.5 vvm of aeration. The fatty acid profiles, evaluated in terms of LED illumination (white, red and blue), showed a predominance of palmitic acid in all cases (59.49%, 57.28% and 46.51%, respectively), which allowed to enhance some biodiesel properties such as cetane number, cold filter plugging point, density and kinematic viscosity, according to international specifications. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Chlorella minutissima; Two-stage cultivation; Microalgae; Bioreactor; Fatty acid; Biodiesel